Management of HR+/HER2+ lobular breast cancer and trends do not mirror better outcomes. (August 2022) - Yaghi, Marita; Bilani, Nadeem; Dominguez, Barbara; Jabbal, Iktej Singh; Rivera, Carlos; Bou Zerdan, Maroun; Li, Hong; Saravia, Diana; Stone, Elizabeth; Nahleh, Zeina
Abstract: Purpose: Treatment protocols for invasive lobular breast cancer (ILC) have largely followed those for invasive ductal breast cancer. This study compares treatment outcomes of endocrine therapy versus combined chemo-endocrine therapy in hormone-receptor-positive (HR+), HER2-positive (HER2+) ILC tumors in a large national registry. Methods: We sampled the National Cancer Database (2010–2016) for female patients with stages I-III, HR+/HER2+ ILC who underwent surgery. Cochran-Armitage trend test examined trends of treatment regimen administration: Surgery only (S), chemotherapy (C), endocrine therapy (ET), and combined chemo-endocrine therapy (CET), with or without anti-HER2 therapy. Cox proportional hazard model were used to compare overall survival (OS) across ET and CET cohorts, stratifying for anti-HER2 therapy, before and after propensity score match of cohorts (2013–2016). Kaplan-Meier (KM) survival curves were also produced. Results: N =11, 421 were included. 58.7% of patients received Anti-Her2 therapy after 2013. CET conferred better OS over ET in the unmatched (adjusted-5-year-OS: 92.5% vs. 81.1%, p<0.001 ) and PS-matched (90.4% vs. 84.5%, p=0.001 ) samples. ET caused lower OS in patients who received Anti-Her2 therapy (HR: 2.56, 95% CI: 1.60–4.12, p<0.001 ) and patients who did not (HR: 1.84, 95% CI: 1.21–2.78, p=0.004 ), as compared to CET on multivariable analysis. KM modeling showed highest OS in the CET cohort who received Anti-Her2 (93.0%), followed by the CET cohort who did not receive Anti-Her2 (90.2%) ( p=0.06 ). Conclusion: Chemotherapy followed by endocrine therapy and Anti-Her2 therapy was shown to be the most effective treatment modality in HR+/HER2+ ILC, contrasting previous data on the inconclusive benefit of chemotherapy in patients with ILC. Highlights: Less chemotherapy (CT) is used in favor of endocrine therapy (ET) alone for HR+/HER2+ ILBC at the expense of efficacy. CT followed by ET remains an effective treatment in HR+/HER2+ ILBC, specifically for larger and locally advanced tumors. Research investigating subgroups of lobular BC who would benefit from CT de-escalation, or ET alone without CT is needed.